Contactless device characterization of transistor structures in silicon using electro optical frequency mapping (EOFM). (March 2020) - Beyreuther, A.; Herfurth, N.; Nakamura, T.; Fischer, G.G.; Keil, S.; Boit, C.
Abstract: Electro-optical frequency mapping (EOFM) is sensitive to carrier densities in electronic devices. Here, parametric measurements of FET and bipolar transistor structures have been performed with EOFM. The Metal-Insulator-Semiconductor (MIS) system of the FET could be characterized for strong inversion and accumulation for estimations of flatband and threshold voltage. Driving the MIS into accumulation also turns on the source/drain pn junctions into forward bias. The carrier profile of the corresponding parasitic bipolar structure is also measured with EOFM showing the different operation modes of a parasitic bipolar junction transistor and the limited performance of the unwanted bipolar parasitic under the FET. For comparison, EOFM results for a vertical high-performance heterojunction bipolar transistors (HBT) in SiGe:C BiCMOS technology are included, showing clearly distinguishable results of a golden and a faulty SiGe:C HBT.